2013
DOI: 10.1007/s40520-013-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated aberrations in mouse cellular and humoral immune responses

Abstract: A decline in cell-mediated immune response, chronic inflammation and aggravation of humoral immunity was evident which conclusively suggests a skewed Th2 pathway during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Data were subjected to two-way analysis of variance (ANOVA) and the Bonferroni test was used to separate the means (P<0.05) which were considered statistically significant. All immunological data are supplemented with respective data of 4 months old young animals (as per Sharma et al 2013b) for better inference of probiotic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were subjected to two-way analysis of variance (ANOVA) and the Bonferroni test was used to separate the means (P<0.05) which were considered statistically significant. All immunological data are supplemented with respective data of 4 months old young animals (as per Sharma et al 2013b) for better inference of probiotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of their respective study period, animals from each set were sacrificed by diethyl ether overdose and blood, peritoneal fluid, spleen, intestine, and liver of the animals were collected to assess various immunological parameters. In order to gain a better understanding of probiotic anti-immunosenescence effects in aging animals (16 months old), all immunological results presented in current investigation have also been supplemented with respective normal data of young (4 months old) animals as earlier investigated in our laboratory (Sharma et al 2013b).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the inflammatory molecules that plays a role in the human ovulatory process and relates to both aging and obesity [14][15][16][17][18][19] is monocyte chemoattractant protein-1 (MCP-1) [20]. MCP-1, a polypeptide composed of 76 amino acids, is produced by various cell types including endothelial cells, fibroblasts, tumor cells, monocytes, and macrophages [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, physiologic levels of MCP-1 are important for the ovulatory process [20]. As far as aging and obesity, data have shown that systemic MCP-1 levels are increased in aging animals [14][15][16] and that there is an increased abundance of this pro-inflammatory chemokine in both white adipose tissue and plasma in obese animals [17][18][19]. Additionally, we have recently demonstrated in women undergoing in vitro fertilization (IVF) that serum and follicular fluid MCP-1 are positively correlated with body mass index (BMI) (Obehi et al, manuscript under review).…”
Section: Introductionmentioning
confidence: 99%